2003
DOI: 10.1073/pnas.1630655100
|View full text |Cite
|
Sign up to set email alerts
|

Development of object concepts in infancy: Evidence for early learning in an eye-tracking paradigm

Abstract: Concepts of objects as enduring and complete across space and time have been documented in infants within several months after birth, but little is known about how such concepts arise during development. Current theories that stress innate knowledge may neglect the potential contributions of experience to guide acquisition of object concepts. To examine whether learning plays an important role in early development of object representations, we used an eye-tracking paradigm with 4-and 6-month-old infants who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
203
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(226 citation statements)
references
References 23 publications
21
203
1
1
Order By: Relevance
“…This indicates that infants can predict action goals of others only when the observed actions of others are within a repertory of actions that the infants themselves can perform. Also, the fact that 4montholds are less capable in anticipating an action goal than older infants is not due a general inability of 4montholds to pre dict future events with their gaze, because 4montholds can predict the reappearance of temporarily occluded objects with their gaze 38,39 . Moreover, we found no significant age differences among 4, 6, 8, and 10month old infants in gazes of BH and MC conditions, indicating that the actual capacity to track objects does not differ among infants of all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that infants can predict action goals of others only when the observed actions of others are within a repertory of actions that the infants themselves can perform. Also, the fact that 4montholds are less capable in anticipating an action goal than older infants is not due a general inability of 4montholds to pre dict future events with their gaze, because 4montholds can predict the reappearance of temporarily occluded objects with their gaze 38,39 . Moreover, we found no significant age differences among 4, 6, 8, and 10month old infants in gazes of BH and MC conditions, indicating that the actual capacity to track objects does not differ among infants of all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…First, older infants produce a greater proportion of oculomotor anticipations (vs. reactive eye movements) relative to younger infants. Johnson, Amso, and Slemmer (2003) presented infants with events in which a small target moved on a horizontal center-occluded trajectory and found that 6-month-olds produced a higher proportion of anticipatory eye movements directed toward the moving target (M = 43.6%) relative to 4-month-olds (M = 29.5%). Gredebäck and von Hofsten (2004) reported continued improvements in predictive tracking up until 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…These early reports demonstrate that there are at least two different ways in which infants can predict the reappearing object; infants can either extrapolate the pre-occlusion trajectory or base their predictions on recent experiences accumulated over successive trials. Subsequent studies of infants' representational abilities have continued to investigate these two modes of prediction (Gredebäck & von Hofsten, 2004;Johnson, Amso, & Slemmer, 2003;Moore & Meltzoff, 2004;Rosander & von Hofsten, 2004;Spelke et al, 1992;von Hofsten, Feng, & Spelke, 2000).…”
Section: Introductionmentioning
confidence: 99%